Trabalhadores sem terra na Amazônia (1970-2020) - Moraes Junior, Leozil Ribeiro de (2021)
This history thesis is about the historical process experienced by landless workers who migrated from the southern states of Brazil, but not exclusively, to the Amazon region in northern Mato Grosso, at the end of the 1970s and beginning of 1980. And how this process elaborated by the authoritarian State of the dictatorial period with supporting companies, disguised in the form of cooperatives, expropriated indigenous people and squatters and concentrated the lands in form of illegal possession in the hands of a few landowners. The thesis approaches how the workers positioned themselves in the face of this capitalist and lying agrarian reform building various political formations of class struggle and began to clashs with representatives of capital, especially state agencies and with the armed militias of land grabbers. For this, I value the memories and interpretations that workers gave of the process they lived and abandon the pretension of proving or disproving a theory or category of analysis, although we are firmly grounded in Marxist and Marxian conceptions. In this process, I verify how the workers built the Rural Workers Syndicate of Novo Mundo to act politically in the struggle for land. And in it not seeking for representation, but representing theyselves and putting pressure on the opposite class and its apparatus. I understood in this way how even there within the working class there were ruptures and conflicts. Then, I argue that the Catholic Church, through the CPT, sought to build itself as another possibility of struggle that conflicted with that one of the syndicate, without contradicting it in essence. Lastly, at times when the working class feels underrepresented by the syndicate and by the CPT, it builds other movements in forms of association that have continued the previous processes. So, I had to approach how these workers moved and still do, among the possibilities of struggle. A relevant issue was the dissolution of the Nhandu Association by the State Justice and with a strong military apparatus of special operations groups, which massacred the leaders and main workers involved in the struggle. In addition to these, the IBAMA in conjunction with the Secretariat of the Environment, criminalized encampments and settlements.